2013
DOI: 10.1002/2013jd020239
|View full text |Cite
|
Sign up to set email alerts
|

Electrification of saltating particles in wind‐blown sand: Experiment and theory

Abstract: [1] The electrification of sand particles is a common phenomenon in wind-blown sand movement. The charge-to-mass ratio of particles is an important parameter to characterize the property of charged particles. However, understanding of the charge-to-mass ratio remains open, and significant discrepancies exist between previous contact electrification models and measurements. This work focuses on the charge-to-mass ratio of saltating particles in wind-blown sand. Experiments were carried out in a wind tunnel usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…We use simple parameterizations from the Lacks and Levandowsky [2007] experiments in our hydrodynamic model to calculate the amount of sand and mineral dust raised in a dust devil. The explicit use of hydrodynamics may add confidence in the meteorology communities' ability to estimate and forecast the amount of material in the atmosphere to be used in global circulation models of the troposphere [Schmidt et al, 1998;Zhang et al, 2003;Arnas et al, 2013]. From the particle charge distribution versus particle radius distribution shown in Lacks and Levandowsky [2007], we can estimate the vertical electric field from the stratification of the particles.…”
Section: 1002/2016jd024832mentioning
confidence: 99%
“…We use simple parameterizations from the Lacks and Levandowsky [2007] experiments in our hydrodynamic model to calculate the amount of sand and mineral dust raised in a dust devil. The explicit use of hydrodynamics may add confidence in the meteorology communities' ability to estimate and forecast the amount of material in the atmosphere to be used in global circulation models of the troposphere [Schmidt et al, 1998;Zhang et al, 2003;Arnas et al, 2013]. From the particle charge distribution versus particle radius distribution shown in Lacks and Levandowsky [2007], we can estimate the vertical electric field from the stratification of the particles.…”
Section: 1002/2016jd024832mentioning
confidence: 99%
“…In addition to affecting dust transport, the E-fields created by charged dust may contribute to detection and early warning of severe dust events. For example, Aizawa et al (2016) and Zhang et al (2017) have documented that the substantial enhancement in the inten-H. Zhang and X. Zheng: Quantifying the large-scale electrification equilibrium effects sity of E-field occurs prior to the arrival of the dust clouds (fronts). Therefore, there is the considerable impetus to investigate electrical effects in dust events.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies are mainly concerned with the vertical profile of E-fields in the near-ground region and their influence on dust transport (e.g., Kamra, 1972;Rudge, 1913;Yair et al, 2016). The measurements showed that the vertical E-fields decrease with increasing height in the sub-meter region (e.g., Schmidt et al, 1998), but exhibit multi-layer properties in the region of up to 30 m height (Zhang et al, 2017). Though measurements of E-fields in dust events are numerous, the measurements associated with the electrical properties of dust particles are relatively sparse.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations